The Living Protection and Inheritance of Jiangzhou Drum Music Based on Field Research - Zhuan, Li Mei (Journal of Roi Kaensarn Academi, 2024)
Jiangzhou Drum Music, also known as Jiangzhou Drum Music, takes drum as the core, uses body language to complement together with drum language, and integrates culture into drum music. It is an excellent model of Chinese folk drum music. However, with the acceleration of China’s urbanization process and the influence of various foreign cultural thoughts, the original environment of the birth of Jiangzhou Drum music no longer exists, and it is urgent to rely on various means to protect and inherit live forms. In this paper through field investigation, in-depth interview research methods analyzes the jiang drum culture change and difficulties, including inheritance fault, drum narrative expression, folk society participation is not high, single protection and inheritance way, etc., on the basis of put forward to strengthen inheritance talent training, dig into its resource value, give play to the leading role of government colleges and universities, digital technology can assign intangible protection measures, power jiang drum intangible living protection and inheritance. The research on this topic further enriches the academic research scope of Jiangzhou Drum music culture, and also provides a reference for the living protection and inheritance of other intangible drum music cultures.